Politics, Interrupted. (March 2019) - Li, Tania Murray
Against the suggestion that we are living in 'post-political' times, I argue that the capacity for critical politics is permanent and broadly distributed, as it emerges from the contradictions embedded in our everyday lives. Yet collective mobilisation to change prevailing power formations is not common. Ethnographers are well positioned to explain why this is so, by investigating critique at its incipient stage, when it may be mute or incoherent, and examining how it develops into a world-changing force or—more often—how the emergence of such a force is interrupted. Posing the trajectory towards historically effective politics as counter-factual (something we might expect to find), and attending to how such a trajectory is interrupted, offers a useful point of entry for ethnographic research. Drawing on the work of Antonio Gramsci and Stuart Hall, I propose a set of questions that could help guide a renewed anthropology of politics along these lines: (1) What is the formation of power that creates a sense of unease, or separation? (2) Through what practices is critique shared or enunciated? (3) What is the social group that connects to this critique? (4) In what ways does a group thus assembled act to change the configuration of power it has identified as problematic? Following the logic of the counterfactual: (5) What potential or embryonic critiques are not articulated, (6) do not form the basis for connection and mobilisation, or (7) do not make new worlds? Finally: (8) What are the formations, practices, and affective states that sustain and stabilise the status quo? In the second part of my essay I use these questions to probe practices of politics in three sites in rural Indonesia where I have carried out research.